2009
DOI: 10.1016/j.curtheres.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recovery characteristics, postoperative nausea and vomiting, and gastrointestinal motility with total intravenous anesthesia with propofol versus inhalation anesthesia with desflurane for laparoscopic cholecystectomy: A randomized controlled study

Abstract: Total intravenous anesthesia with propofol and alfentanil was associated with a significantly reduced rate of PONV and analgesic consumption, shortened recovery time and duration of hospitalization, accelerated onset of bowel movements, and increased patient satisfaction compared with desflurane and alfentanil in these patients undergoing laparoscopic surgery who completed the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
2
30
1
Order By: Relevance
“…Studies with greater precision appear as larger circles. As described below equation (10), the standard error is calculated by dividing the width of the 75% confidence interval by the corresponding inverse of the standard normal distribution. This graph is novel because previous studies did not estimate the standard error of the reduction in variability for each study in which desflurane was compared with sevoflurane and isoflurane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with greater precision appear as larger circles. As described below equation (10), the standard error is calculated by dividing the width of the 75% confidence interval by the corresponding inverse of the standard normal distribution. This graph is novel because previous studies did not estimate the standard error of the reduction in variability for each study in which desflurane was compared with sevoflurane and isoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…Following equation (10), the generalized pivotal statistic for the logarithm of the ratios of the standard deviations 54 is…”
Section: Meta-analysismentioning
confidence: 99%
“…A total of 13 trials reported pain intensity at or around 2 h postsurgery, in which 686 patients received anaesthesia using propofol for maintenance, while 668 were given inhalational anaesthesia [10,11,[18][19][20][21][22][23][24][25][26][27][28]. Overall, pain scores were not significantly different between experimental groups (Hedge's g (95%CI) À0.120 (À0.415-0.175) (p = 0.425) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies investigated postoperative nausea and vomiting, with 371 patients receiving propofol and 354 patients receiving inhalational anaesthesia [10,19,20,22,24,25,28,30]. Propofol was associated with a significant reduction in postoperative nausea and vomiting (relative risk (95% CI) 0.446 (0.304-0.656) (p < 0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because it brings little damage and interference to internal organs and patients can recover quickly afterwards, LC has become the first operation choice for biliary tract diseases. However, the increased excitement of gastrointestinal sympathetic nerves, inhibited gastrointestinal function, and subsequent decreased gastrointestinal peristalsis and tension led by operation anesthesia, peritoneal stimulation, and traction during operation are possible to cause corresponding complications [4][5][6][7][8] . Therefore, it's of great significance to restore gastrointestinal function in promoting the post-operative recovery.…”
Section: Discussionmentioning
confidence: 99%